Definiowanie narkomanii - ciągłość czy zmiana? = Defining drug-addiction: continuity or change? - Bazuń, Dorota (Zielona Góra: Lubuskie Towarzystwo Naukowe)
From the viewpoint of a constructivist perspective, social problems emerge not due to tensions in social structure but because people define a given situation as problematic. Such an approach is employed in this article, which presents the relation between the changing ways of defining the problem of drug-addiction and the strategies of counteracting it. This is exemplified using the case of Monar - Poland`s biggest organisation providing help and assistance to drug-addicts.
Keywords: narkomania; Monar; organizacja pozarządowa